(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Haematobiochemical changes of ovine (sheep) blood were investigated during preservation and storage with Citrate Phosphate Dextrose Adenine-1 (CPDA-1) and Acid Citrate Dextrose (ACD) for transfusion. Twelve healthy sheep were selected and divided into two equal groups: group X (n=6) and group Y (n=6). Thirty-five ml of blood was collected from each animal and preserved with CPDA-1 in group X and ACD in group Y under 4°C in refrigerator for 28 days. Haematological changes viz., total erythrocyte count (TEC), total leukocyte count (TLC), haemoglobin (Hb), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC); and biochemical changes viz., total protein (TP) and pH were evaluated immediately after blood collection and thereafter on day-1, day-3, day-7, day-14, day-21 and day-28 for both groups. In ACD preserved blood; TEC, TLC, Hb and PCV decreased significantly (P<0.01) from day-14 onward, whereas in CPDA-1 preserved blood, these parameters decreased significantly (P<0.01) from day-21 onward. Blood preserved in ACD showed significant changes (P<0.01) in MCV, MCH and MCHC respectively from day- 7, day-14 and day-21 onward, whereas blood preserved in CPDA-1 showed no significant changes in the same parameters throughout the experiment. In both groups, no significant changes were noticed in TP but significant changes (P<0.01) were observed in pH with the progression of storage period. These findings elicited that both ACD and CPDA-1 exert certain haematobiochemical changes in stored sheep blood, however, CPDA-1 was more efficient than ACD in terms of maintaining proper levels of TEC, TLC, Hb., PCV, MCV, MCH and MCHC during preservation and storage of sheep blood for transfusion. Res. Agric., Livest. Fish.7(1): 113-120, April 2020